2009
DOI: 10.1021/ja902677t
|View full text |Cite
|
Sign up to set email alerts
|

Studies for the Synthesis of Xenicane Diterpenes. A Stereocontrolled Total Synthesis of 4-Hydroxydictyolactone

Abstract: The stereocontrolled total synthesis of 4-hydroxydictyolactone (4), a member of the xenicane diterpene family of natural products, is described. These studies feature the development of the B-alkyl Suzuki cross-coupling reaction for direct access to (E)-cyclononenes from acyclic precursors. The Ireland-Claisen rearrangement is effectively utilized to establish the backbone asymmetry of the contiguous C2, C3, C10 stereotriad of 4. The synthesis strategy has devised an intramolecular Nozaki-Hiyama reductive ally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 71 publications
5
35
0
1
Order By: Relevance
“…497 They utilized a cross-coupling protocol to construct a macrocycle from highly functionalized late stage intermediate 173 . During their optimization, they observed a significant influence of the protecting group on the reaction outcome.…”
Section: Applications Of Alkyl Organometallic Reagents In Total Symentioning
confidence: 99%
“…497 They utilized a cross-coupling protocol to construct a macrocycle from highly functionalized late stage intermediate 173 . During their optimization, they observed a significant influence of the protecting group on the reaction outcome.…”
Section: Applications Of Alkyl Organometallic Reagents In Total Symentioning
confidence: 99%
“…349 This same alga was also the source of the cadinane sesquiterpenes 306 and 307, and six other known cadinanes. 355 The inhibitory activity of two known dolastanes from Dictyota cericornis (Baia da Ribeira, Brazil) against mammalian Na + K + -ATPase was evaluated. 352 In a study of a Mediterranean Dictyota sp.…”
Section: Brown Algaementioning
confidence: 99%
“…Consequentially,w ea ssumed that the alcohol might be too burdened in its steric environmentt o affect the envisaged transformation. Indeed, exposing alkyne 65 to Bu 3 SnSiMe 3 under Pd catalysis gave rise to as ingle regioisomer 66.S ubsequent iododestannylation( I 2 ,2 ,6-di-tert-butyl-4-methylpyridine, À40 8C) [66] and treatment with Me 2 CuLi delivered alkenyl silane 67.T oaccess the macrocyclization precursor 60,w et reated silane 67 with excess N-iodosuccinimide (NIS) ( % 2.5 equivalents) in MeCN to affect an iododesilylation. Upon isolation of an ew product, 1 HNMR spectroscopy revealed that the iododesilylation took place as indicated by ad ownfield shift of the alkenyl proton from d = 5.20 to 5.89 ppm.…”
Section: The B-alkylsuzuki Approachmentioning
confidence: 99%